FLIPPED CLASSROOM METHOD APPLIED IN TEACHING PHRASEOLOGICAL UNITS - Azimbayeva Dilafruz Abdujabbarovna (Western European Studies, 2025)
The article examines the application of the flipped classroom method in teaching phraseological units (idioms, collocations, fixed expressions) in foreign language learning. It provides a theoretical overview of the flipped method, discusses the linguistic and cultural complexity of phraseological units, and evaluates the compatibility of flipped instruction with phraseological teaching goals. Drawing on research in EFL education, the article reviews empirical studies demonstrating that flipped learning enhances student engagement, autonomy, communicative competence, and motivation. Although little research directly explores the flipped model for phraseology, the paper argues that the method is well-suited to address challenges of idiom acquisition by allowing self-paced pre-class exposure and intensive inclass communicative practice. A methodological model— “Flipped-Interactive Phraseology Course”—is proposed, offering practical steps for pre-class, in-class, and post-class instruction. The article concludes by identifying limitations and proposing directions for future research.
Keywords: Flipped classroom; phraseological units; idioms